2012
DOI: 10.5098/hmt.v3.1.3005
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Drop Measurements With Boiling in Diverging Microchannel

Abstract: An experimental study of flow boiling through diverging microchannels has been carried out in this work, with the aim of exploring reduction in flow instabilities during boiling in diverging microchannels. Effect of mass flux, heat flux and divergence angle on two phase pressure drop has been studied using deionized water as the working fluid. The experiments are carried out on three test sections with divergence angle of 4, 8 and 12 deg with nearly constant hydraulic diameter (146, 154 and 157 µm respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The microchannel with inlet restrictor showed less instability and performed well at the higher heat flux. The reduction in flow boiling instability using diverging microchannel was studied by Agrawal et al [6]. Three different divergence angles of 4, 8 and 12 were studied which showed that the pressure drop and instability reduce during flow boiling in microchannel with divergence angle of 12.…”
Section: Introductionmentioning
confidence: 99%
“…The microchannel with inlet restrictor showed less instability and performed well at the higher heat flux. The reduction in flow boiling instability using diverging microchannel was studied by Agrawal et al [6]. Three different divergence angles of 4, 8 and 12 were studied which showed that the pressure drop and instability reduce during flow boiling in microchannel with divergence angle of 12.…”
Section: Introductionmentioning
confidence: 99%
“…Hsieh et al (2013) used a heated converging-diverging microchannel to stretch DNA molecules using thermoelectrophoresis and convection. Some efforts have also been made to reduce flow boiling instabilities by employing a diverging microchannel (Agrawal et al, 2012;Lee and Pan, 2008). Xuan et al (2005) employed converging-diverging microchannel for particle separation using electrophoretic separation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Pan (2008) employed a diverging microchannel to reduce flow instability during flow boiling in the microchannel. Agrawal et al (2012) and Duryodhan et al (2013a) performed boiling experiments on diverging microchannels with various divergence angles and found that diverging microchannels are useful for reducing boiling flow instability. Stemme and Stemme (1993) fabricated and tested a novel valve-less micropump using a nozzle-diffuser arrangement in brass metal.…”
Section: Introductionmentioning
confidence: 99%